A self‐controlled study of intralesional injection of diprospan combined with topical timolol cream for treatment of thick superficial infantile hemangiomas. Issue 3 (30th April 2018) - Xu, Peng; Yu, Qian; Huang, Huizhen; Zhang, Wenjie; Li, Wei
Abstract: Topical application of timolol cream is effective and convenient for treating superficial infantile hemangiomas. Intralesional injection of corticosteroids, such as diprospan, is useful for the treatment of superficia infantile hemangiomas without systemic side effects. We conducted a self‐controlled study to investigate whether a combination of intralesional injection of diprospan with topical timolol 0.5% cream would be more efficient than timolol cream alone in thick superficial infantile hemangiomas. Thirty‐eight patients with 39 thick superficial infantile hemangiomas were recruited. Each lesion was randomly divided into two equal parts: one part was treated with topical timolol 0.5% cream (timolol cream group), while the other part was treated with injection of diprospan combined with topical timolol 0.5% cream (combined treatment group). Infants were followed every 4 weeks to determine whether injections should be continued, and timolol cream was applied four times daily for 5 months. During 5 months of treatment, three specialist physicians were invited to evaluate the therapeutic effects. The combined treatment group showed better lesion involution than did the timolol cream group regarding lesion thickness and color of lesions. The combination of intralesional injection of diprospan with topical timolol 0.5% cream is a suitable and safe strategy for thick superficial infantile hemangiomas.